Polypoid Endometriosis – A mimic of malignancy - Ghafoor, Soleen (Abdom Radiol (NY), 2020)
This an interesting case of an asymptomatic 60-year-old postmenopausal patient with an incidental pelvic mass mimicking a pelvic malignancy on imaging. Biopsy revealed findings consistent with polypoid endometriosis. After discontinuation of hormone replacement therapy, the mass showed decrease in size on follow-up imaging. Polypoid endometriosis is a rare but distinct variant of endometriosis with histopathologic features akin to an endometrial polyp. Clinical and imaging features of polypoid endometriosis differ from classic endometriosis. While classic endometriosis predominates in premenopausal women, polypoid endometriosis more commonly affects peri- to postmenopausal women and is associated with the exposure to Tamoxifen or hormone replacement therapy. Imaging features that aid in the differential diagnosis of polypoid endometriosis are a T2 hyperintense polypoid mass with signal characteristics similar to uterine endometrium, a T2 hypointense peripheral rim, contrast enhancement pattern mirroring the enhancement of the uterine endometrium, and lack of diffusion restriction. Radiologists should be familiar with polypoid endometriosis because this clinically and morphologically distinct variant may mimic malignant neoplasms on imaging.